(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article on the basis of sculptural samples the creation of museums and memorials outside the country is analyzed through the activity of the National Museum of Azerbaijan Literature named after Nizami Ganjavi. From the beginning of its creation, the museum has always provided close assistance to the creation, reconstruction and improvement of museums with a literary profile. The bringing of the tombstone of one of the founders of the Azerbaijan Democratic Republic Alimardan bek Topchubashov to the country and replacing it with a new monument is considered as an object of research. The article also mentions the importance of the Mehdi Huseynzade Memorial Museum in Slovenia and the monument in the museum erected in his honor. Here we consider the classification of the public aspect of sculptural samples, as well as their functions as museum items. All the exhibits of Mehdi Huseynzade in his memorial museum are shown to the audience against the background of emotional impact. This merit of the Nizami Museum is propagandistic, it strengthens friendship and cooperation between countries and positively influences the establishment and development of cultural and political relations. The presentation of historical psychological themes through sculptural patterns shows the continuous development of the historical genre as a historical and artistic source. Key words: memorials, memorial museum, sculpture, museology.